2018
DOI: 10.3748/wjg.v24.i7.870
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal metastasis of stem cell-subtype hepatocholangiocarcinoma: Rare presentation of a rare tumor

Abstract: Hepatocholangiocarcinoma (cHCC-ICC) is a rare primary hepatic tumor defined by the presence of histological features of both hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). Its prevalence ranges from 1%-5% of all primary liver cancers. We report the case of a 55-year-old cirrhotic male patient admitted to our university hospital for dysphagia, revealing a 10 cm lower-third esophageal metastasis of an unresectable cHCC-ICC with stem-cell features. Computed tomography and abdominal magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Harada et al, reported a case of asymptomatic oesophageal metastasis, found on routine basis, in a patient with hepatocellular carcinoma, that underwent an oesophagectomy with thoracotomy and the biopsy showed metastasis from hepatocellular carcinoma, whereas, Salimon et al, reported a case of symptomatic oesophageal metastasis in a patient with hepatocholangiocarcinoma and dysphagia. The patient was treated with chemotherapy, contrary with the previous one [6,10]. Nugroho and Serra et al, reported cases of adrenal gland metastases from primary hepatocellular carcinoma, diagnosed with CT-guided biopsy, that were treated with chemotherapy [11,12] whereas, Zhigui Li et al, reported a case of a patient with multiple ectopic liver tissues along the pancreas, with development of hepatocellular carcinoma on these [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Harada et al, reported a case of asymptomatic oesophageal metastasis, found on routine basis, in a patient with hepatocellular carcinoma, that underwent an oesophagectomy with thoracotomy and the biopsy showed metastasis from hepatocellular carcinoma, whereas, Salimon et al, reported a case of symptomatic oesophageal metastasis in a patient with hepatocholangiocarcinoma and dysphagia. The patient was treated with chemotherapy, contrary with the previous one [6,10]. Nugroho and Serra et al, reported cases of adrenal gland metastases from primary hepatocellular carcinoma, diagnosed with CT-guided biopsy, that were treated with chemotherapy [11,12] whereas, Zhigui Li et al, reported a case of a patient with multiple ectopic liver tissues along the pancreas, with development of hepatocellular carcinoma on these [15].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hepatocellular carcinoma varies among geographical areas, with greater incidence being found in Asia, Taiwan, Korea, China and Japan [1][2][3][4][5][6][7]. Advanced hepatocellular carcinoma is one of the most lethal diseases and includes metastases to various organs, such as lungs, lymph nodes, musculoskeletal structures, peritoneal surface, gastrointestinal tract, spleen and pancreas [7][8][9][10]. It has only few systematic therapeutic options, with Sorafenib, being the most important pos administered molecular drug, that increases overall survival by approximately 3 months (10.7 months) compared with placebo (7.7 months) [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations